2009
DOI: 10.1136/gut.2009.186775
|View full text |Cite
|
Sign up to set email alerts
|

Long-term proton pump induced hypergastrinaemia does induce lineage-specific restitution but not clonal expansion in benign Barrett's oesophagus in vivo

Abstract: While the short-term effects of gastrin enhance epithelial restitution in Barrett's oesophagus (but not squamous mucosa) there is no clinical evidence that Barrett's oesophagus length expands over time. This study, which is the largest and longest term randomised controlled trial of gastrin biology in Barrett's oesophagus, is further proof of the clinical safety of PPI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
(44 reference statements)
1
19
0
1
Order By: Relevance
“…Several studies have suggested that Barrett’s epithelium has increased expression of CCK2R and that gastrin is able to stimulate proliferation in Barrett’s epithelium. Although PPI therapy and hypergastrinemia seem to increase proliferation in the short term, there is no evidence of long-term harm due to pharmacological acid suppression [52,53,54]. Furthermore, an ex vivo study has demonstrated that intermittent acid exposure has antiproliferative effects on an in vitro population of non-neoplastic immortalized Barrett’s cell line.…”
Section: Acid Suppressionmentioning
confidence: 99%
“…Several studies have suggested that Barrett’s epithelium has increased expression of CCK2R and that gastrin is able to stimulate proliferation in Barrett’s epithelium. Although PPI therapy and hypergastrinemia seem to increase proliferation in the short term, there is no evidence of long-term harm due to pharmacological acid suppression [52,53,54]. Furthermore, an ex vivo study has demonstrated that intermittent acid exposure has antiproliferative effects on an in vitro population of non-neoplastic immortalized Barrett’s cell line.…”
Section: Acid Suppressionmentioning
confidence: 99%
“…Although serum gastrin levels increased significantly in the study participants, the length of Barrett's metaplasia did not change in either the low-or high-dose PPI groups, suggesting that PPI effects on serum gastrin levels might not have important clinical effects in patients with Barrett's esophagus. 24 Some epidemiologic studies have found an association between PPI use and esophageal adenocarcinoma, but this association is likely to be the spurious result of a confounding-by-indication bias. Because GERD and Barrett's esophagus are risk factors for esophageal adenocarcinoma, and because PPIs are often prescribed for patients with GERD and Barrett's esophagus, an association between PPIs and esophageal adenocarcinoma might not be caused by the drug, but rather by the underlying conditions for which the PPIs were prescribed.…”
Section: Potential Carcinogenic Effects Of Proton Pump Inhibitors In mentioning
confidence: 98%
“…В результаті проведених досліджень встановлено, що після 28 днів введення омепразолу концентра-ція гастрину в сироватці крові зростала в 3,1 раза (p<0,05) (рис. 1), що корелює з даними інших авто-рів про зростання секреції даного гормону як після короткотривалого [4], так і після довготривалого застосування інгібіторів протонної помпи [6,7,10].…”
unclassified